2015
DOI: 10.5326/jaaha-ms-6093
|View full text |Cite
|
Sign up to set email alerts
|

Porcupine Quill Migration in the Thoracic Cavity of a German Shorthaired Pointer

Abstract: A 7 yr old German shorthaired pointer presented with progressive respiratory distress and lethargy. Two weeks prior to presentation, the dog had porcupine quills removed from the left forepaw, muzzle, and sternal area. At the time of presentation, the dog had bounding pulses and friction rubs in the right dorsal lung field. Harsh lung sounds and decreased lung sounds were ausculted in multiple lung fields. Radiographs revealed a pneumothorax and rounding of the cardiac silhouette suggestive of pericardial effu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 5 publications
0
43
0
Order By: Relevance
“…The authors believe these radial keratin structures are what could be seen as multiple hyperechoic lines within the quill. Echocardiography appears to be a good modality for detecting intra-cardiac migratory quills, but few cases have been described (Costa et al 2014 ; Guevara et al 2015 ; Nucci & Liptak 2016 ). Ultrasound imaging is obviously limited by bone or air interfaces (Mattoon & Nyland 2015 ), with further visualisation of the cranial quill in our case not being possible, despite being suggestive of vertebral canal location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors believe these radial keratin structures are what could be seen as multiple hyperechoic lines within the quill. Echocardiography appears to be a good modality for detecting intra-cardiac migratory quills, but few cases have been described (Costa et al 2014 ; Guevara et al 2015 ; Nucci & Liptak 2016 ). Ultrasound imaging is obviously limited by bone or air interfaces (Mattoon & Nyland 2015 ), with further visualisation of the cranial quill in our case not being possible, despite being suggestive of vertebral canal location.…”
Section: Discussionmentioning
confidence: 99%
“…A case of an intra-cranial porcupine quill described the HU as ranging from 52 to 68 (Sauvé et al 2012 ), which is markedly lower than 115–160 as found in our study. Another report on thoracic, including intra-cardiac, migration of quills, reported that they exhibited a soft tissue attenuation (HU not given) that made detection difficult, and thus a quill within a cardiac chamber was missed (Guevara et al 2015 ). A third report (Costa et al 2014 ) also could not detect an intra-cardiac quill.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of intrathoracic foreign bodies, resulting from a penetrating thoracic injury [ 5 , 8 , 11 , 15 , 19 , 20 ], migration of an implant such as a Kirschner wire [ 6 , 10 ], or migration of a foreign body from the respiratory [ 2 ] or gastrointestinal tract [ 4 , 12 , 13 , 23 , 26 ], is not often reported in small animals. Wooden foreign bodies such as kebab or popsicle sticks are often ingested by dogs because of their palatability, and given their length and sharply pointed ends, can easily migrate from the gastrointestinal tract.…”
mentioning
confidence: 99%
“…JL Guevara et al (7) reported that porcupine spike had migrated to the heart after penetrating the thorax.…”
Section: Discussionmentioning
confidence: 99%